ANALISIS PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PESERTA PROGRAM JAMINAN SOSIAL TENAGA KERJA PT. JAMSOSTEK (PERSERO) CABANG BALI - Ni Ketut Rendi Astuti; Ni Nyoman Sri Ratnawati (STIMI Handayani Denpasar, 2015)
In this industrialized period and more tight competition in labour fieldnow, it is a field that has sufficient attention for the Government such as wagesand protection for labours. Human Resources is the main capital for companyand it is an abligatory duty for every company to deliver social service to labours.Jamsostek as one of state owned company (BUMN) that carries for labour socialservice program has shown its commitment to give economic social protection tolabours. The aim of this study is to know service quality toward client satisfaction oflabour social service of PT. Jamsostek (Pesero) Bali Branch. The analysis techniqueapplied to know whether there is or no correlation between service quality and clientsatisfaction, is analysis technique of Rank Sperman Correlation.Based on analysis result of client satisfaction, it is obtained average score 3.22 percent,it means that client satisfaction of labour social guarantee program PT. Jamsostek(Persero) Bali Branch is categorized satisfying, and also service quality is obtainedfor average score 3.18 percent, it means service qualityPT. Jamsostek (Persero)Bali Branch is categoeized satisfying. In relations with the result of interpolationcalculation, it is obtained rho calculation = 0.905 > Rho table = 0.371. Due torho calculation is higher than rho table, it means that there is a strong correlationbetween service quality and client satisfaction of labour social guanateen programPT. Jamsostek (Pesero) Bali Branch.